Plant homocysteine, a methionine precursor and plant’s hallmark of metabolic disorders - Sobieszczuk-Nowicka, Ewa; Arasimowicz-Jelonek, Magdalena; Tanwar, Umesh Kumar; Floryszak-Wieczorek, Jolanta (Frontiers in Plant Science, 2022)
Homocysteine (Hcy) is a sulfur-containing non-proteinogenic amino acid, which arises from redox-sensitive methionine metabolism. In plants, Hcy synthesis involves both cystathionine β-lyase and S-adenosylhomocysteine hydrolase activities. Thus, Hcy itself is crucial for de novo methionine synthesis and S-adenosylmethionine recycling, influencing the formation of ethylene, polyamines, and nicotianamine. Research on mammalian cells has shown biotoxicity of this amino acid, as Hcy accumulation triggers oxidative stress and the associated lipid peroxidation process. In addition, the presence of highly reactive groups induces Hcy and Hcy derivatives to modify proteins by changing their structure and function. Currently, Hcy is recognized as a critical, independent hallmark of many degenerative metabolic diseases. Research results indicate that an enhanced Hcy level is also toxic to yeast and bacteria cells. In contrast, in the case of plants the metabolic status of Hcy remains poorly examined and understood. However, the presence of the toxic Hcy metabolites and Hcy over-accumulation during the development of an infectious disease seem to suggest harmful effects of this amino acid also in plant cells. The review highlights potential implications of Hcy metabolism in plant physiological disorders caused by environmental stresses. Moreover, recent research advances emphasize that recognizing the Hcy mode of action in various plant systems facilitates verification of the potential status of Hcy metabolites as bioindicators of metabolism disorders and thus may constitute an element of broadly understood biomonitoring.